Staphylococcus pseudintermedius for CAMP-test - Savini, Vincenzo (e-Century Publishing Corporation, 2014)
CAMP test reliably detects Listeria monocytogenes (Lm) and Streptococcus agalactiae (group B streptococcus, GBS); it is traditionally performed streaking the tested isolate perpendicularly to Staphylococcus aureus (Sa), provided that reference Sa strains (that produce β-hemolysin) are used. In a zone of β-hemolysin activity, in fact, GBS and Lm form typical arrow-shaped hemolytic areas. While Sa production of the toxin is strain-dependent, however, that of Staphylococcus pseudintermedius (Sp), a pet-owner colonizer and an emerging human pathogen, is constitutive, then observed in all clinical isolates. Therefore, Sp may indeed represent a valid alternative to perform the assay.